Efficacy of environmental friendly disinfectants against the major postharvest pathogens of stone fruits on plastic and wood surfaces. (March 2019) - Bernat, M; Casals, C; Teixidò, N; Torres, R; Carballo, BC; Usall, J
Disinfection of surface facilities during postharvest handling operation is an important practice to avoid secondary fruit infections at stone fruit packinghouses. The aim of this work was to evaluate the effect of six environmental friendly disinfectants against Monilinia fructicola, Penicillium expansum, Rhizopus spp., and Alternaria spp. on plastic and wood surfaces. Hydrogen peroxide, peracetic acid, sodium hypochlorite, Mico-E-pro®, Proallium FRD-N®, and DMC Clean-CNS® were used as the disinfectants. Untreated and surfaces treated with water were used as controls. Plastic and wood surfaces were sampled with Rodac plates at 2 and 24 h after treatments and the number of colonies were counted. In general, all disinfectants reduce the number of viable conidia from all studied surfaces. Hydrogen peroxide used in a concentration of 150 mg L −1 was the less effective disinfectant in all studied pathogens. The commercial product Mico-E-pro® composed of oregano, onion, and orange extract at a dose of 10 mg L −1 was the most effective disinfectant. Rhizopus spp. was the pathogen more resistant to the disinfectants followed by P. expansum, M. fructicola, and Alternaria spp. Water decreased the number of conidia adhered to the surface. In addition, the untreated control showed substantial conidia reduction after 24 h of artificial inoculation.